The Relationship of Experiential Avoidance, Familial Emotional Atmosphere and Self-Control with Online Gaming Addiction in Bachelor Student of Shahid Chamran University of Ahvaz - Arash Zandipayam; Iran davoudi; Mahnaz Mehrabizadeh (Hamadan University of Medical Sciences, 2016)
Background and Objectives: online game addiction is considered as a compulsive, excessive, uncontrollable and destructive physical and psychological behavior. With regard to the problem of persons with addiction to online gaming in the fields of experiential avoidance, families emotional atmosphere and self-control, this study was carried out with the aim of determining the relationship of experiential avoidance, families emotional atmosphere and self-control with online gaming addiction in the bachelor student of Shahid Chamran University of Ahvaz. Materials and Methods: The research design was descriptive and correlational, performed on 200 bachelor student of Shahid Chamran University of Ahvaz, Iran. Sampling was conducted using multi-stage random sampling. Information were collected via SPSS 16 and to analyze the data, Pearson's correlation and regression (inter) tests were used. Results: The results showed a significant positive correlation in familial emotional atmosphere and experiential avoidance with addiction to online games and there was a significant negative correlation between self-control and addiction to online games. Regression analysis indicated that familial emotional atmosphere determined 28% of the variance of addiction to online games. Conclusions: The results confirmed the relationship of addiction to online games with familial emotional atmosphere and experiential avoidance, also emphasized on the importance of family environment in intensified use of internet. The results of this study can be used to plan appropriate interventions, including awareness among students and practitioners in the field of symptoms and consequences of addiction to online games, and try to correct the use of internet among users, to prevent and effectively manage this disorder.